SEQUENCE BIOSTRATIGRAPHY OF LATE OLIGOCENE - EARLY MIOCENE CARBONATE ROCK, UJUNG PANGKAH FIELD, NORTHEAST JAVA BASIN - Muhammad, Faisal
Ujung Pangkah field is located in offshore Gresik district, East Java Province. Ujung Pangkah field has been producing hydrocarbons from carbonate reservoir (Late Oligocene – Early Miocene). Reservoir heterogeneity in carbonate is very diverse. It can affect the production performance and strategy of field development. Therefore, identification of reservoir heterogeneity is very important for further research. Reservoir heterogeneity in carbonate reservoir is related to depositional environment and sea level change. Depositional environment and sea level change can be analyse using sequence biostratigraphy. Analysis of sequence biostratigraphy was carried out by integrating biostratigraphy, well log, petrography, core-cutting and image log data. Identification of sequence boundary is correlated with decreasing of microfossil assembling. It is also supported by increasing secondary porosity (vuggy) based on petrography (core and cutting) and image log. Identification of maximum flooding surface is correlated with maximum increasing of deeper biofacies, such as Cycloclopeous spp., Lepidocyclina spp. and planktonic. Based on analysis of sequence biostratigraphy, Late Oligocene – Early Miocene carbonate reservoir interval can be divided into 4 sequences. Sequence 1 (25.2 – 24 Ma) is dominated by carbonate rocks (coral foram grainstone - packstone) with open platform - organic build up depositional environment. Sequence 2 (24 – 21 Ma) is dominated by carbonate rock (foram alga packstone - wackstone) which gradually changes into carbonate rock - interbedded claystone with restricted platform - upperforeslope depositional environment. Sequence 3 (21 – 19.8 Ma) is dominated by dominated by claystone with some presence of carbonate rock (foram alga packstone - wackstone) with upper foreslope depositional environment. Sequence 4 (19.8 – 16 Ma) is dominated by dominated claystone with some presence of carbonate rock (foram alga packstone - wackstone) with restricted platform – upper foreslope depositional environment.